Molecular mechanisms involved in the bidirectional relationship between diabetes mellitus and periodontal disease - Harpreet Singh Grover; Shailly Luthra (Wolters Kluwer Medknow Publications, 2013)
Both diabetes and periodontitis are chronic diseases. Diabetes has many adverse effects on the periodontium, and conversely periodontitis may have deleterious effects further aggravating the condition in diabetics. The potential common pathophysiologic pathways include those associated with inflammation, altered host responses, altered tissue homeostasis, and insulin resistance. This review examines the relationship that exists between periodontal diseases and diabetes mellitus with a focus on potential common pathophysiologic mechanisms.